158 Provision of artificial shade before weaning influences performance of Angus and Brangus cow-calf pairs. (30th November 2020) - da Silva, Gleise Medeiros; Schulmeister, Tessa M; Podversich, Federico; Tarnonsky, Federico; Zamora, Maria E; Urrutia, Juan I; Laporta, Jimena; Batista Dubeux, Jose Carlos; Gonella-Diaza, Angela M; DiLorenzo, Nicolas
Abstract: A completely randomized design study with a 2 × 2 factorial arrangement of treatments evaluated the impact of artificial shade (SHADE or NO SHADE) and breed (ANGUS vs. BRANGUS) on performance of cows, nursing calves, and subsequent offspring. Twenty-four Angus and 24 Brangus black-hided pregnant cows (579 ± 8 kg BW; 6.5 yr; approximately 85 d of gestation) and their nursing calves were randomly allocated to 12 'Pensacola' bahiagrass pastures (Paspalum notatum Flüggé; 1.3 ha; n = 4 pairs/pasture), with or without access to artificial shade (NO SHADE BRANGUS [NSB], NO SHADE ANGUS [NSA], SHADE BRANGUS [SB], and SHADE ANGUS [SA]) for 56 d during summer. Body condition score (BCS) of cows and BW of pairs were obtained on d -1, 0, 55, and 56 (weaning weight). Following weaning, calves were randomly allocated to 4 pens (n = 12/pen) equipped with GrowSafe feed bunks for 14 d to measure feed intake (DMI) and efficiency (G:F). A shade × breed interaction (P < 0.05) was observed for average daily gain (ADG) and BCS of cows, with SB being greatest (P ≤ 0.05). Pre-weaning calf ADG tended to be greater (P = 0.10) for SHADE vs. NO SHADE. Weaning weight and BW 14-d post-weaning were lesser for NSB vs. NSA, SA, and SB, whereas no differences in DMI, ADG, or G:F were observed (P > 0.11). Gestation length was greater for SHADE vs. NO SHADE cows (292 vs. 274; P = 0.02), but calf birth weight was not different. Providing artificial shade to pregnant-lactating beef cows positively impacted the growth of Brangus but not Angus cows. However, weaning BW of calves from Angus cows regardless of shade access did not differ from that of Brangus calves with shade. Further research should investigate the potential long-term effects of shade on the subsequent offspring.